El acogimiento familiar en Iberoamérica (2023)
Foster care is one modality for the alternative care of children and teenagers without parental care. The objective of this study is to carry out a systematic review of foster care in Latin America. The method used was the search in databases such as PubMed, Scopus, SciELO, PsycINFO, with information published between 2010 and 2017. Ninety-one evidences were included, observing that family fostering in Latin America is being implemented. One of the crucial aspects is the terminology used by different countries. In the types of foster care in Latin America, foster care in extended and surrogate families prevails. It was observed that each Latin American country has a regulatory body of public policies and protection. There are few scientific publications related to family fostering in Honduras, Nicaragua, Salvador, Bolivia, and Venezuela, from the Caribbean Islands, this is observed mainly in Haiti and other countries such as Cuba, Puerto Rico, and the Dominican Republic. Otherwise, this is not observed in Brazil, Colombia, Chile, Guatemala, Peru, and Spain. Family fostering in Latin America develops gradually. The countries analyzed have ratified the Convention on the Rights of the Child, except Puerto Rico. Therefore, they recognize the right of the child to live with the family through the implementation of the Guidelines on alternative care. © 2018, UNIV SAOPAULO. All rights reserved.